Analysis of the Economic Potential of Tuna By-Products: A Case Study of Morotai Island, North Maluku (Agrikan Jurnal Agribisnis Perikanan, 2024)
The tuna industry in Pulau Morotai holds significant economic potential. However, its utilization has primarily focused on tuna loin, while byproducts (waste) remain largely underutilized. This study aims to identify and analyze the economic potential of tuna byproducts in Pulau Morotai Regency. Data was collected from PT Harta Samudera during 2020-2022, encompassing tuna production, byproduct types, and volumes. The findings reveal that tuna waste accounts for 40.90% of the total tuna body weight. This waste comprises heads (15.45%), bones (10.45%), viscera (6.82%), and skin (3.64%). The estimated potential for processing tuna waste into fishmeal reaches 61,282.5 kg per year, with an economic value of Rp 1,225,650,000. Processing this waste can enhance the income of fishermen and fish processing industries, reduce environmental pollution, and support food security.
Keywords: Tuna; Limbah; Tepung Ikan; Potensi Ekonomi; Pulau Morotai